OBN seismic data PP- and PS-waves joint inversion and reservoir characterization - Li, Fang; Liu, Shiyou; Wang, Rui; Tang, Yuyuan; Chen, Shuangquan (Frontiers in Earth Science, 2025)
The use of seismic exploration data to invert shear (S-) wave information plays a very important role in oil and gas exploration, especially in reservoir prediction with increasingly complex lithology and deeper target layers. Combining longitudinal (P-) and S-waves information can help us better describe reservoirs. In theory, to obtain accurate shear wave information through inversion, we will need shear or converted wave (PS-wave) data to be used in a joint inversion. The propagation of S-wave in underground media is different from that of P-wave, as S-wave are mainly influenced by the rock skeleton and less affected by pore fluids. As a result, we propose a joint prestack seismic inversion method for PP- and PS-waves data based on L1-2-norm constraints. Firstly, a joint coefficient matrix is constructed using linear approximation equations for the reflection coefficients of PP- and PS-wave. Next, the L1-2-norm constraint is introduced to construct the inversion objective function, and a two-steps iterative strategy is applied for optimization, achieving a three-parameter prestack inversion. In the synthetic data testing, different models are used for inversion comparison. The synthetic data inversion results show that compared with traditional norm constrained methods or PP-wave inversion alone, the proposed joint inversion method can invert results with higher correlation coefficients and lower errors, confirming the accuracy and stability of the proposed method. Finally, the proposed method is applied to offshore OBN multi-component seismic data. The well and seismic joint comparative analysis of the inversion results shows that the inversion results are reliable, and compared with PP-wave inversion alone, the results provide higher resolution and better continuity, enabling more accurate prediction of reservoirs.